Antioxidant properties of fruit seeds as valuable source for functional food ingredients and nutraceutical products - Senawi, Norshazila; Kamarudin, Kamarul Rahim; Syed Osman Idid, Syed Zahir Idid; Mohamed Rehan, Aisyah; Koya, Mustapha Suleiman (2008)
This study was conducted to determine the potential of fruit waste materials as sources of natural antioxidant. Seeds are major byproducts during the processing of fruits-based products such as puree, canned slices, juice and pickles. Normally, the seeds will be discarded as waste since they are not currently utilized for any commercial purposes. The seed extracts of guava (Psidium guajava), mango (Mangifera indica L.) and papaya (Carica papaya L.) were analyzed in this study for total phenolic content, free radical scavenging activity and metal ion chelating activity. The dried seeds were extracted with 70% ethanol. The solvents were removed using rotary evaporator and the extracts containing the residual moisture were freeze-dried. Total phenolic content was evaluated according to Folin- Ciocalteu procedure. The amount of total phenolic content was calculated as gallic acid equivalents from the calibration curve. Generally, the results showed that mango seed extracts relatively had higher total phenolic content followed by guava and papaya, by which the mango seed extracts contained 320 mg/l of phenolic compound, the guava seed extracts with 200 mg/l of phenolic compound and the papaya seed extracts indicated the least total phenolic content of 80 mg/l. Furthermore, the antioxidant activity was evaluated based on the ability of the seed extracts to scavenge 2, 2-diphenyl-2-picrylhydrazil (DPPH). Among the seed extracts, mango showed the highest percentage of scavenging activity up to 80% at 0.2mg/ml, followed by guava and papaya. Moreover, all the seed extracts showed ferrous ion chelating (FIC) activity in the range of 34.06% to 45.81% at 0.10 mg/ml. Overall, the current data showed that all seed extracts contained a number of antioxidant compounds, which have the ability to scavenge free radicals and chelate metal ions under in vitro conditions. Therefore, the fruit seeds can be considered as sources of natural antioxidant in nutraceutical and functional food.